Graphene oxide complex as a pH-sensitive antitumor drug. Issue 13 (11th February 2015) - Cheng, Rumei; Zou, Ruitao; Ou, Shengju; Guo, Rui; Yan, Ruiying; Shi, Haiyan; Yu, Shanshan; Li, Xiaojian; Bu, Yexu; Lin, Mimi; Liu, Yong; Dai, Liming
Abstract : A chitosan-xanthone-GO nanocomposite as a pH-sensitive nanocarrier for controlled release of the antitumor drug. Abstract : A pH-sensitive, nanostructured antitumor drug, GO-CONH-Schiff base (GCS), was prepared from the chitosan-xanthone Schiff base (CS)-modified graphene oxide (GO) complex. The successful synthesis of GCS was confirmed using various spectroscopic techniques, including FT-IR, XPS, UV-vis and TGA. The resulting GCS showed superb antitumor activity with the pH-sensitive release of the antitumor part, CS, and decreased cytotoxicity of GCS to normal human cells. The release of CS was stable and thorough in the solution at pH 1 (the pH value for gastric juice), suggesting that the as-synthesized, pH-sensitive drug could provide new insights into the design of advanced nanostructured oral drugs.